2016
DOI: 10.1007/s12144-016-9452-0
|View full text |Cite
|
Sign up to set email alerts
|

Development and Validation of Adolescent Comparative Body and Appearance Satisfaction Scale (ACBASS)

Abstract: A large number of studies have investigated body image and appearance-related social comparisons among college students and adolescents. However, there is no adolescent-specific instrument for measurement of body and appearance satisfaction within social context. The present study aimed to develop and validate Adolescent Comparative Body and Appearance Satisfaction Scale (ACBASS). Three studies (n = 938) were conducted to investigate validity and reliability of the scale. Finally, a 20-item scale with 4 compon… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
5
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 71 publications
(69 reference statements)
1
5
0
Order By: Relevance
“…Only three studies have analyzed the psychometric properties of the BAS-2 among children (Halliwell, Jarman, Tylka, & Slater, 2017) and adolescents (Alcaraz-Ibá ñez et al, 2017;Lemoine et al, 2018) and, to the best of our knowledge, no study has been conducted with geriatric populations over the age of 65. In line with the reported data in adult samples, findings in children and adolescents on the BAS and BAS-2 reflected the adaptive properties of body appreciation for body-related and psychological well-being (Atari et al, 2016;Halliwell et al, 2017;Lemoine et al, 2018;Lobera & Ríos, 2011;Moreira, Lorenzato, Neufeld, & Almeida, 2018). However, it remains unclear whether sex and age moderates body appreciation levels during these developmental stages.…”
Section: Introductionsupporting
confidence: 83%
See 1 more Smart Citation
“…Only three studies have analyzed the psychometric properties of the BAS-2 among children (Halliwell, Jarman, Tylka, & Slater, 2017) and adolescents (Alcaraz-Ibá ñez et al, 2017;Lemoine et al, 2018) and, to the best of our knowledge, no study has been conducted with geriatric populations over the age of 65. In line with the reported data in adult samples, findings in children and adolescents on the BAS and BAS-2 reflected the adaptive properties of body appreciation for body-related and psychological well-being (Atari et al, 2016;Halliwell et al, 2017;Lemoine et al, 2018;Lobera & Ríos, 2011;Moreira, Lorenzato, Neufeld, & Almeida, 2018). However, it remains unclear whether sex and age moderates body appreciation levels during these developmental stages.…”
Section: Introductionsupporting
confidence: 83%
“…Its associations with eating behavior were also found to be in a positive direction with intuitive eating (Pálmarsdóttir & Karlsdóttir, 2016;Tylka & Wood-Barcalow, 2015a) and in a negative direction with maladaptive eating behavior (Swami, García et al, 2017;Torres, Barbosa, Meneses, Tylka, & Vieira, 2018). Measures of general wellbeing are documented with a positive relationship between BAS-2 scores and self-esteem, life satisfaction (e.g., Atari, Jamali, Bahrami-Ehsan, & Mohammadi, 2016;Namatame et al, 2017;Swami, García et al, 2017;Swami & Ng, 2015;Swami et al, 2016;Swami, García et al, 2017;Torres et al, 2018), positive life orientation (Alleva et al, 2016;Razmus & Razmus, 2017), positive affect (Razmus & Razmus, 2017;Torres et al, 2018), and proactive coping (Tylka & Wood-Barcalow, 2015a). BAS-2 scores made an incremental contribution to self-esteem (Alleva et al, 2016;Namatame et al, 2017;Torres et al, 2018;Tylka & Wood-Barcalow, 2015a), eating behavior (Namatame et al, 2017;Tylka & Wood-Barcalow, 2015a), proactive coping (Tylka & Wood-Barcalow, 2015a), and satisfaction with life (Namatame et al, 2017) over other positive body image-related constructs, providing evidence for its incremental validity.…”
Section: Introductionmentioning
confidence: 97%
“…Interest in aesthetic rhinoplasty was not associated with age, BMI, or birth order; however, our findings indicate that media consumption could be a potential predictive factor for considering this cosmetic procedure. 44,45 Differential validity of IARS was also assessed in study 3 using a case-control design. Results showed that those who desired aesthetic rhinoplasty had significantly higher scores on all items of the IARS.…”
Section: Discussionmentioning
confidence: 99%
“…Fourth, women (but not men) who reported low facial feature esteem and men (but not women) who held beliefs that facial appearance perfection is attainable reported making more upward comparisons of facial attractiveness (Franzoi et al, 2012). Moreover, making more downward comparisons of facial attractiveness was associated with higher selfesteem, a more positive outlook on life in general, more body appreciation, and less interest in a rhinoplasty (Atari et al, 2017).…”
Section: Who Makes Social Comparisons Of Facial Attractiveness Most O...mentioning
confidence: 91%